2011
DOI: 10.1111/j.1872-034x.2011.00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety in sitagliptin therapy for diabetes complicated by chronic liver disease caused by hepatitis C virus

Abstract: Our results indicate that sitagliptin is effective and safe for the treatment of T2DM complicated with HCV positive chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
3
13
0
1
Order By: Relevance
“…Our previous study has showed that sitagliptin therapy is effective and safe for chronic hepatitis C patients with T2DM . The present study suggests that sitagliptin therapy is effective and safe for NAFLD patients with T2DM.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our previous study has showed that sitagliptin therapy is effective and safe for chronic hepatitis C patients with T2DM . The present study suggests that sitagliptin therapy is effective and safe for NAFLD patients with T2DM.…”
Section: Discussionsupporting
confidence: 64%
“…Our previous study has showed that sitagliptin therapy is effective and safe for chronic hepatitis C patients with T2DM. 27 The present study suggests that sitagliptin therapy is effective and safe for NAFLD patients with T2DM. Regarding efficacy, the improvement of HbA1c level at 48 weeks after the initiation of sitagliptin was 0.9% in patients with hepatitis C virus and 0.7% in those with NAFLD.…”
Section: W E Have Described the Efficacy And Side-effectssupporting
confidence: 49%
“…The efficacy of sitagliptin therapy has been shown in patients with T2DM complicated by NAFLD [27][28][29][30] , NASH [31] or CLD caused by hepatitis C virus [32] . However, one report suggested that NAFLD may adversely affect the glycaemic control obtained with sitagliptin [33] .…”
Section: Hepatic Safetymentioning
confidence: 99%
“…The study concluded that sitagliptin is effective and safe for the treatment of T2DM complicated with HCV positive CLD. [80] In an observational pilot study, paired liver biopsies from 15 patients with diabetes and NASH before and after 1 year of therapy with sitagliptin 100 mg once daily were studied. Sitagliptin resulted in a significant decrease in ballooning and NASH scores, while the reduction in the steatosis score was of borderline statistical significance.…”
Section: Methodsmentioning
confidence: 99%